The Effects of Technical Barriers to Trade on Export of Textiles and Garments from Bangladesh to the USA - Md-Iqbal Bhyuan; 오근엽 (무역연구, 16(6), 2020)
Purpose - Given the importance of the T&G sector in Bangladesh, and the potential effects of TBTs on this sector, the main objective of this paper is to measure the effects of TBTs on export of Bangladeshi T&G goods to the USA. Design/Methodology/Approach - We employ the PPML estimator to quantify the effects of US TBTs on Bangladeshi T&G exports. The frequency index and coverage ratio were used to quantify restrictions imposed by TBTs. We performed 294 observations; we studied 14 cross sections of T&G items classified using HS descriptors 50-63 over the 21 years from 1995 to 2015. Findings - This paper found that both the frequency index and coverage ratio measuring TBT, significantly (and positively) impacted Bangladesh T&G exportsto the USA. We used the Granger test to explore a possible causal relationship between the US TBTs and the Bangladeshi T&G export volume. The causality test confirms that a substantial surge in Bangladeshi T&G exports triggered the US TBT notifications. The dummy variable MFA coefficients were both positive and significant, indicating that the quota system contributed to the growth of Bangladeshi T&G exportsto the USA. Research Implications - Our empirical results have important implications for Bangladeshi T&G producers, exporters, and policy makers that technical regulations can enhance export growth and sustainable economic development if Bangladesh can build consumer confidence by ensuring the quality and safety of exports. KCI Citation Count: 1